2019
DOI: 10.1007/s00217-019-03231-1
|View full text |Cite
|
Sign up to set email alerts
|

Deproteinated potato wastewater as a low-cost nitrogen substrate for very high yeast biomass quantities: starting point for scaled-up applications

Abstract: The aim of this research was to investigate the influence of deproteinated potato wastewater (DPW) supplemented by different initial concentrations of glucose on biomass yield, especially lipids biosynthesis and fatty acids composition. DPW is a low-cost source of nitrogen and other biogenic elements. It allowed for an efficient yeast cells growth and a very high biomass yield of Rhodotorula glutinis var. rubescens LOCKR13. A short time of incubation leads to a biomass rich in protein, which can be a source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The composition of fatty acids influences the intended use, so if the goal is to produce biodiesel, there should be a high proportion of SFAs. Then the final product has appropriate properties, such as cetane number (CN), flash point (FP), and viscosity (µ) [8]. If SCO has a nutritionally proper fatty acid content, it can be used for food production [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of fatty acids influences the intended use, so if the goal is to produce biodiesel, there should be a high proportion of SFAs. Then the final product has appropriate properties, such as cetane number (CN), flash point (FP), and viscosity (µ) [8]. If SCO has a nutritionally proper fatty acid content, it can be used for food production [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that strain Rhodotorula glutinis var. rubescens can grow efficiently (biomass yield 39.52 g L −1 ) in deproteinated potato wastewater and glucose medium [8], and after fed-batch cultivation, the content of lipids in biomass exceed >34% d.w. [10]. Except for accumulated fat in intracellular lipid droplets, the cells are also rich in proteins, carbohydrates, and carotenoids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Deproteinated potato wastewater (DPW) is a liquid waste of the starch industry (over 12 million m 3 /year) [8], which can be a source of nitrogen in the media used for yeast biomass growth and the biosynthesis of microbial oils [23]. The high productivity depends not only on the possibilities of the strain to accumulate lipids in lipid bodies but also on biomass yield [20].…”
Section: Introductionmentioning
confidence: 99%